2018
DOI: 10.1039/c8tc00679b
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogen radical enhanced atomic layer deposition of TaOx: saturation studies and methods for oxygen deficiency control

Abstract: Investigations of saturation behaviors of growth rate and valence band states in TaOx (tantalumethoxide and plasma-activated hydrogen) ALD process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 32 publications
0
8
0
Order By: Relevance
“…The proposed approach allowed for the determination of a specific V O concentration, which results in the best match between the ab initio calculation and the VB XPS spectra. This approach has already been utilized for estimating the stoichiometry of other ALD-grown films. , The calculations were carried out within the density functional theory framework with the hybrid exchange-correlation parameterization functional GauPBE using the periodic three-dimensional cell approximation within Quantum ESPRESSO software . A plane-wave basis set with a cutoff energy of 1020 eV and optimized norm-conserving Vanderbilt pseudopotentials were used for these calculations.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The proposed approach allowed for the determination of a specific V O concentration, which results in the best match between the ab initio calculation and the VB XPS spectra. This approach has already been utilized for estimating the stoichiometry of other ALD-grown films. , The calculations were carried out within the density functional theory framework with the hybrid exchange-correlation parameterization functional GauPBE using the periodic three-dimensional cell approximation within Quantum ESPRESSO software . A plane-wave basis set with a cutoff energy of 1020 eV and optimized norm-conserving Vanderbilt pseudopotentials were used for these calculations.…”
Section: Methodsmentioning
confidence: 99%
“…In active oxygen-based PEALD processes, however, the active oxygen must perform somewhat contradictory tasks: (1) removing the organic ligands and (2) achieving oxygen deficiency in the growing metal oxide films, which makes precise control of the process tricky. Another interesting approach was suggested by Egorov et al that utilized an oxygen-containing precursor (tantalum ethoxide) and Ar/H 2 plasma discharge. , However, the oxygen-containing precursors can only be employed for a limited number of oxides because some of the relevant metals lack appropriate oxygen-containing metal precursors for facile ALD, including W, which is the topic of this work.…”
Section: Introductionmentioning
confidence: 99%
“…It is attributed to the presence of V 0 , which formed localized states in the bandgap. [ 17–19 ] The XPS VB TaO x film spectrum was described by theoretical spectra for Ta 2 O 5 with an oxygen vacancy in 126‐atom supercell (solid line in Figure 2). The main discrepancy between the theory and the experiment is due to the calculation model simplicity, namely, the fact that the exact values of the photoionization cross section are taken as weight factors when summing PDOS, and this probably leads to an overestimation of the Ta5 d orbitals contribution (≈9 eV) relative to O2 p .…”
Section: Resultsmentioning
confidence: 99%
“…In this regard, the authors recently reported a new way of depositing TaO x ( x < 2.5) films via a radical‐enhanced atomic layer deposition (REALD). [ 17–19 ] The RS cell fabricated using a single layer of REALD grown TaO x in combination with extracting Ta electrode showed highly desirable electroforming‐free resistance switching performance up to six·10 6 cycles with no sign of degradation. [ 18 ] Although the absence of switching current modulation with the cell area suggests the filamentary RS, it has not been studied in detail.…”
Section: Introductionmentioning
confidence: 99%
“…This is because the switching layer in the oxide‐based ReRAM requires the incorporation of an appropriate level of defects, typically oxygen vacancies ( V O ) . In this regard, the authors recently reported a method of depositing Ta 2 O 5 films containing appropriately controlled V O concentrations via the radical enhanced ALD (REALD) process using Ta‐ethoxide (Ta(OC 2 H 5 ) 5 ) and active radicals generated by a remote Ar/H 2 plasma mixture as the Ta‐precursor and reactant, respectively . A prototypical ReRAM TiN/TaO x /Ta 2 O 5 /Pt cell based on combining the stoichiometric Ta 2 O 5 and non‐stoichiometric TaO x ( x < 2.5) that showed highly favorable resistance switching (RS) performance up to 10 6 cycles was fabricated .…”
mentioning
confidence: 99%